SAT0021 Both Gray-Scale Synovial Hypertrophy and Synovial Power Doppler Signals on a Comprehensive Ultrasound Scan are the Predictive Factors of Relapse After Discontinuation of Biological Agents in Patients with Rheumatoid Arthritis. (23rd January 2014) - Iwamoto, T.; Ikeda, K.; Hosokawa, J.; Yamagata, M.; Tanaka, S.; Sanayama, Y.; Nakagomi, D.; Okubo, A.; Takahashi, K.; Hirose, K.; Sueishi, M.; Nakajima, H.
Abstract : Background: Clinical information does not accurately predict relapse after discontinuation of biological agents in patients with rheumatoid arthritis (RA). Although ultrasound is a sensitive tool to detect sub-clinical synovial inflammation in RA patients with low disease activity, the ultrasound findings on the unilateral hand did not discriminate between patients who relapsed and who did not after discontinuation of TNF antagonists in the previous report 1 . Objectives: This pilot, single-blinded, prospective study aimed to determine whether the comprehensive ultrasound scan on 40 joints is informative in the prediction of relapse after discontinuation of biological agents. Methods: RA patients in remission states (DAS28 ≤ 2.6) receiving biological agents who agreed to discontinue the biological agent were recruited. Patients underwent a comprehensive ultrasound scan on 40 joints (DAS28 joints + ankles + MTP joints) and were prospectively followed up for 26 weeks. The physicians who evaluated the patients during the study period were blinded to the ultrasound findings at baseline. Results: Thirty patients receiving either TNF antagonists (n = 24), or tocilizumab (n = 6) were enrolled. The disease activity was very low (median DAS28 1.64 [IQR 1.2-2.3]) before the biological agent was discontinued. Eleven patients had relapse which was defined as DAS28 > 3.2 and restarted receiving the same biological agent within 26 weeks. Total ultrasound scores provided with larger areas under the ROC curves for the prediction of relapse than DAS28 did. Using the optimal cut-off values determined by the ROC analysis, the PPV and NPV of total GS score ≥ 12 to predict flare were 88% and 82%, respectively. On the other hand, the PPV and NPV of total PD score ≥ 3 were 100% and 79%, respectively. Image/graph: Conclusions: In RA patients with very low disease activity receiving biological agents, a comprehensive ultrasound scan provides good diagnostic values to predict relapse after discontinuation of the biological agent. References: Saleem B, Keen H, Goeb V, Parmar R, Nizam S, Hensor EM, et al. Patients with RA in remission on TNF blockers: when and in whom can TNF blocker therapy be stopped? Ann Rheum Dis 2010;69(9):1636-42. Disclosure of Interest: T. Iwamoto: None Declared, K. Ikeda Grant/research support from: Mitsubishi-Tanabe Pharma Corporation, Abbott Japan Co., Ltd, Consultant for: Mitsubishi-Tanabe Pharma Corporation, Abbott Japan Co., Ltd, J. Hosokawa: None Declared, M. Yamagata: None Declared, S. Tanaka: None Declared, Y. Sanayama: None Declared, D. Nakagomi: None Declared, A. Okubo: None Declared, K. Takahashi: None Declared, K. Hirose: None Declared, M. Sueishi: None Declared, H. Nakajima Grant/research support from: Mitsubishi-Tanabe Pharma Corporation, Chugai Pharmaceutical Co., Ltd, Consultant for: Mitsubishi-Tanabe Pharma Corporation, Chugai Pharmaceutical Co., Ltd